2012
DOI: 10.1155/2012/187585
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Rational Design of an Asymptomatic Clinical Herpes Vaccine: The Old, the New, and the Unknown

Abstract: The best hope of controlling the herpes simplex virus type 1 and type 2 (HSV-1 and HSV-2) pandemic is the development of an effective vaccine. However, in spite of several clinical trials, starting as early as 1920s, no vaccine has been proven sufficiently safe and efficient to warrant commercial development. In recent years, great strides in cellular and molecular immunology have stimulated creative efforts in controlling herpes infection and disease. However, before moving towards new vaccine strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
80
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(84 citation statements)
references
References 132 publications
3
80
1
Order By: Relevance
“…4,16,25,26,[28][29][30][31][32][33] We wanted to determine whether in vivo immunization with these human ASYMP CD8 þ T-cell epitopes induces frequent and polyfunctional HSV-specific CD8 þ T cells that reduce herpetic corneal disease. Using the new ''humanized'' HLA-Tg rabbit model of ocular herpes infection and disease, we characterized the T-cell immunogenicity and protective efficacy of nine human ASYMP CD8 þ T-cell epitopes that we recently identified from three major HSV-1 Ags, namely, gB, tegument proteins VP11/12, and VP13/14.…”
Section: Discussionmentioning
confidence: 99%
“…4,16,25,26,[28][29][30][31][32][33] We wanted to determine whether in vivo immunization with these human ASYMP CD8 þ T-cell epitopes induces frequent and polyfunctional HSV-specific CD8 þ T cells that reduce herpetic corneal disease. Using the new ''humanized'' HLA-Tg rabbit model of ocular herpes infection and disease, we characterized the T-cell immunogenicity and protective efficacy of nine human ASYMP CD8 þ T-cell epitopes that we recently identified from three major HSV-1 Ags, namely, gB, tegument proteins VP11/12, and VP13/14.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Many factors can increase the risk of HSV-2 reactivation such as stress, fatigue, sun exposure, surgery, infection, fever, and menstrual periods. 5 A study of 457 consecutive patients with HSV-2 isolated from genital lesions reported that patients who had primary HSV-2 infections lasting 35 or more days had a recurrence rate 1.83 times greater than those who had shorter initial HSV-2 infections (mean 0.66 vs 0.36 recurrences month, p D 0.001). 2 HSV-2 reactivation rates were also about 20% higher in men than women.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In this regard it is worth mentioning that mice are not considered good models to study reactivation since mice do not suffer recurrent episodes. 11 The vaccines were also expected to provide strong protection in humans but many such attempts have failed for some of the reasons discussed in this article. Likewise, therapeutic vaccines also needed to reduce the risk of transmission, but none showed consistent success in reducing symptoms or viral shedding.…”
Section: Introductionmentioning
confidence: 99%